Dynamics of the α-relaxation during the crystallization of PLLA and the effect of thermal annealing under humid atmosphere. (June 2019) - Makrani, N.; Ammari, A.; Benrekaa, N.; Rodrigue, D.; Giroux, Y.
Abstract: The purpose of this work is to study the crystallization of transparent and amorphous poly-l -lactic acid (PLLA) as a function of temperature and thermal history under fixed frequencies. The effect of thermal annealing under humid atmosphere was investigated with respect to temperature and time. The crystallization was found to be achieved upon a very broad exothermic peak in the range of 82–137 °C, involving the formation of α′ (∼102 °C) and α (∼115 °C) structures. The dielectric strength increases with increasing temperature above ∼100 °C, and varies with the thermal history of the film. The dielectric loss data during crystallization, was depicted as a relaxation process involving two unresolved relaxation peaks; while the dielectric polarization at low frequency involves long-range segmental motions and the relaxation is only observed following a second run. At higher frequencies, the α′-process disappears with increasing temperature and the α-process becomes dominant. The crystalline dipoles seem to be more tightly bound and respond differently due to the thermal history preceding the crystallization. The chain mobility decreases and the long-range segmental motions is suppressed, shifting the relaxation toward higher frequencies and higher temperatures. The infrared characteristics bands are found to be sensitive to disorder and thermal history. Furthermore, the structural change and the chain mobility during crystallization significantly affect the electron charge distribution and shift the electronic spectra. The change in the physical properties of the material are correlated with the films crystallization and molecular weight reduction. For longer annealing time and higher temperature, the crystallization decreases the aging effect and improves both the thermal and mechanical stability. Highlights: Loss data depicted a relaxation process comprising two unresolved relaxation peaks. At higher frequencies, α′-process disappears and the α-relaxation becomes dominant. Characteristics bands are sensitive to disorder and thermal history. The physical properties are correlated with the crystallization and the weight drop. Thermal annealing initiate the crystallization, which reduces the physical aging.